1991
DOI: 10.1126/science.1843843
|View full text |Cite
|
Sign up to set email alerts
|

Massive Cortical Reorganization After Sensory Deafferentation in Adult Macaques

Abstract: After limited sensory deafferentations in adult primates, somatosensory cortical maps reorganize over a distance of 1 to 2 millimeters mediolaterally, that is, in the dimension along which different body parts are represented. This amount of reorganization was considered to be an upper limit imposed by the size of the projection zones of individual thalamocortical axons, which typically also extend a mediolateral distance of 1 to 2 millimeters. However, after extensive long-term deafferentations in adult prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
527
7
11

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,034 publications
(564 citation statements)
references
References 22 publications
19
527
7
11
Order By: Relevance
“…There is no intrinsic, hard-wired, link between a location in a somatotopic map and a body location. This is especially true given Body Beyond SI 9 the clear plasticity of somatotopic maps following peripheral trauma (Merzenich et al, 1984;Pons et al, 1991) and learning Pascual-Leone & Torres, 1993). While some referral of sensation between skin surfaces may occur following massive cortical reorganisation (e.g., Ramachandran, Rogers-Ramachandran, & Stewart, 1992) or in plasticity induced by simultaneous tactile co-activation of skin surfaces (Schweizer et al, 2001;Sterr et al, 1998), in most cases plastic changes in somatosensory cortex do not lead to mislocalsation of touch.…”
Section: Localisation Of Touch On the Body Surfacementioning
confidence: 99%
“…There is no intrinsic, hard-wired, link between a location in a somatotopic map and a body location. This is especially true given Body Beyond SI 9 the clear plasticity of somatotopic maps following peripheral trauma (Merzenich et al, 1984;Pons et al, 1991) and learning Pascual-Leone & Torres, 1993). While some referral of sensation between skin surfaces may occur following massive cortical reorganisation (e.g., Ramachandran, Rogers-Ramachandran, & Stewart, 1992) or in plasticity induced by simultaneous tactile co-activation of skin surfaces (Schweizer et al, 2001;Sterr et al, 1998), in most cases plastic changes in somatosensory cortex do not lead to mislocalsation of touch.…”
Section: Localisation Of Touch On the Body Surfacementioning
confidence: 99%
“…This plasticity allows the neocortex to adapt to changes in the environment, to loss of function in the sensory periphery or along the subcortical pathways that bring the sensory world to the neocortex. Plastic changes occur in the adult primate cortex following disuse or peripheral injury (Buonomano and Merzenich, 1998;Garraghty and Muja, 1995;Merzenich and Sameshima, 1993;Pons et al, 1991;Wall et al, 2002). Cortical plasticity has also been reported in humans with referred phantom sensations after spinal cord injury (Mackert et al, 2003;Moore et al, 2000).…”
mentioning
confidence: 93%
“…For example, after dorsal rhizotomy of one upper limb, the sensory input from the ipsilateral face starts activating the deafferented 'hand region' of the adjacent S1 cortex. 3 The finding by this author that such changes in topography occur also in human patients with phantom limbs has had striking perceptual consequences. [4][5][6][7][8][9] Furthermore, phantom arms that are 'paralysed' or 'frozen' in an awkward, sometimes painful, position can often be reanimated by the simple device of using visual feedback to convey the illusion that the phantom is moving in response to the brain's command.…”
mentioning
confidence: 94%
“…Following the early work of Patrick Wall, 1 experiments on the somatosensory cortex of monkeys 2,3 showed that there is a tremendous latent plasticity in the adult primate brain. For example, after dorsal rhizotomy of one upper limb, the sensory input from the ipsilateral face starts activating the deafferented 'hand region' of the adjacent S1 cortex.…”
mentioning
confidence: 99%